Surface preparation effect on duplex stainless steel passive film electrical properties studied by in situ CSAFM. Issue 20 (18th August 2015) - Guo, L.Q.; Yang, B.J.; Liang, D.; Qiao, L.J.
Abstract: Abstract : The effect of surface preparation—grinding, polishing, and electrochemical etching—on the duplex stainless steel passive film conductivity was investigated by in situ current sensing atomic force microscopy. The current maps show that the current in the passive film on three prepared surfaces is different, especially for the ferrite and austenite phase surface. The current on the austenite and ferrite is similar on either mechanical ground or polished surfaces, but the current on the austenite surface is much higher than current on the ferrite surface after electrochemical etching. The difference in the passive film conductivity originates from the changes in the chemical composition and thickness of the passive film and the change in topographical properties induced by the preparation procedures. This is confirmed by AFM, x-ray photoelectron spectroscopy, and auger electron spectroscopy measurements.